Information and Communication Technology (ICT) Utilization Patterns among Small Ruminant Farmers in West Bengal - Dhara, Chandra; Tiwari, Rupasi; Negi, Shikhakriti; Chander, Mahesh; Dutt, Triveni (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
India’s increasing demand for livestock products, driven by a 70% non-vegetarian population and rising meat consumption, is expected  to surge by 2050. Meeting this demand necessitates a 3-fold rise in meat production. Small ruminants like goats and sheep are crucial,  especially for landless and small farmers. However, constraints such as inadequate veterinary services, poor market access, and limited  awareness of scientific practices hinder productivity. With the country’s rapid digitalization, ICT tools offer promising solutions. A study of  120 small ruminant farmers in West Bengal found WhatsApp to be the most commonly used tool (100%), followed by YouTube (89.57%),  Face book (82.67%), and Television. WhatsApp was accessed daily by all farmers. However, adoption was limited by high costs (mean  score 79.99), lack of relevant content (60.6), and language barriers (54.59). Despite these challenges, expanding smartphone usage and  affordable data are boosting ICT penetration in rural areas. The study highlights the potential of digital platforms to improve knowledge  dissemination, veterinary services, and market linkages. Strengthening digital infrastructure and integrating AI-driven advisory systems  can significantly enhance sustainable livestock production in India.
Keywords: Digital tools; ICT adoption; ICT Utilization pattern; Sheep and Goat; Small ruminants